1994
DOI: 10.1002/mrd.1080380303
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of segregation in a human male reciprocal translocation carrier, t(1;11) (p36.3;q13.1) by two‐colour fluorescence in situ hybridization

Abstract: Using centromeric probes specific for chromosomes 1 and 11, 13,071 sperm nuclei from a male reciprocal translocation heterozygote, 46,XY,t(1;11) (p36.3;q13.1), were analyzed by fluorescence in situ hybridization (FISH). Decondensed sperm nuclei were simultaneously hybridized with DNA probes for chromosome 1 (pUC177) and chromosome 11 (D11Z1). Results were as follows: 1/11 (82.45%), 1/1/- (3.45%), -/11/11 (4.85%), 1/1/11 (1.20%), 1/11/11 (1.14%), 1/- (4.33%), -/11 (2.50%), 1/1/11/11 (0.06%), 1/1/1/- (0.02%). Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 18 publications
1
33
0
1
Order By: Relevance
“…Although statistical differences were found in the FISH system, no significant differences between 22,N and 24,N chromosomes were observed in the human ± hamster analysis (w 2 test, P=0.4156). The excess of 3 : 1 hypohaploidies over 3 : 1 hyperhaploidies has also been observed in other twocolour FISH 26 and three-colour FISH studies. 28 Other works 22,29 indicated that technical artefacts could explain these apparent discrepancies: the sperm head is small, and as a result the number of probes that can be individually scored is limited.…”
Section: European Journal Of Human Geneticssupporting
confidence: 73%
See 3 more Smart Citations
“…Although statistical differences were found in the FISH system, no significant differences between 22,N and 24,N chromosomes were observed in the human ± hamster analysis (w 2 test, P=0.4156). The excess of 3 : 1 hypohaploidies over 3 : 1 hyperhaploidies has also been observed in other twocolour FISH 26 and three-colour FISH studies. 28 Other works 22,29 indicated that technical artefacts could explain these apparent discrepancies: the sperm head is small, and as a result the number of probes that can be individually scored is limited.…”
Section: European Journal Of Human Geneticssupporting
confidence: 73%
“…(2) FISH on sperm nuclei has higher statistical resolution than sperm chromosome complement analysis (6524 sperm nuclei versus 352 chromosome complements). However, it is important to point out that the number of chromosome complements analysed by previous comparative studies 13,26,27 ranged from 72 to 542, and no significant differences between both types of analysis were found. (3) Technical limitations of both analysis.…”
Section: European Journal Of Human Geneticsmentioning
confidence: 87%
See 2 more Smart Citations
“…Sperm karyotypes are able to evaluate separately the result of the different segregation modes. FISH studies in dual colour, using in most cases centromeric probes for the chromosomes involved in the translocation, do not allow to differentiate alternate and adjacent-1 segregants (Spriggs and Martin 1994;Rousseaux et al 1995;Mennicke et al 1997;Estop et al 1997;Mercier et al 1998;Giltay et al 1999). One exception was the translocation (7;8)(q11;q21;cen) reported by Mercier et al (1998).…”
Section: Discussionmentioning
confidence: 99%